Peran Komite Madrasah dalam Meningkatkan Mutu Pendidikan di Madrasah Ibtidaiyah Hidayatul Atfal Batu Samban - Mastun, Mastun; Fitriana, Iin Mahlia; Najamuddin, Najamuddin; Ali, Lalu Usman; Faqih, M. (Yayasan Alpatih Harapan Semesta, 2025)
This study examines the role of the School Committee in enhancing education quality at MI Hidayatul Atfal Batu Samban, West Lombok, during 2023. Employing a descriptive qualitative method through observation, interviews, and documentation, findings show that the committee performs three essential functions: (1) supporting through financial assistance, infrastructure, and learning activities; (2) advising by providing input for programs and management; and (3) controlling by monitoring program implementation and fund accountability. Key challenges include limited community economic capacity, low parental awareness, and inadequate skills among committee members. To overcome these, the committee strengthens communication with school leadership, promotes self-help initiatives, and encourages community participation. The study highlights the importance of collaboration among committees, school leaders, teachers, and the community, recommending capacity building and stronger regulatory support to sustain improvements.